Therapists’ Expressions of Agreement in Therapeutic Conversations With Chinese Children With ASD: Strategies, Sequential Positions and Functions - Zeng, Xiaorong; Ma, Bosen; Li, Chenxi; Zhang, Laiyun; Li, Chenxi; Li, Haifeng (Frontiers in Psychology, 2022)
Based on conversations between 10 Chinese children with Autism Spectrum Disorders (ASD) and five therapists in the context of Naturalistic Intervention, this study investigated the therapists’ agreement expressions in this typical setting. The study found that (1) the therapists mainly used four agreement strategies: acknowledgment, positive evaluation, repetition and blending. These four strategies could be used individually or in combination. The first three strategies and their combinations were used frequently during the therapeutic conversation. (2) With the major occurrences in the post-expansion position, the agreement expressions in the therapeutic conversation mainly performed three functions, namely, creating a supportive therapeutic relationship, serving as positive reinforcers and implementing interventions pertinent to communication skills. (3) This study proposed that the therapists’ preferred use of agreement expressions in the intervention process could be explained by the features of Naturalistic Intervention.